BTLA/HVEM Signaling: Milestones in Research and Role in Chronic Hepatitis B Virus Infection - Yu, Xueping; Zheng, Yijuan; Mao, Richeng; Su, Zhijun; Zhang, Jiming (Frontiers in Immunology, 2019)
B- and T-lymphocyte attenuator (BTLA) is an immune-regulatory receptor, similar to CTLA-4 and PD-1, and is mainly expressed on B-, T-, and all mature lymphocyte cells. Herpes virus entry mediator (HVEM)-BTLA plays a critical role in immune tolerance and immune responses which are areas of intense research. However, the mechanisms of the BTLA and the BTLA/HVEM signaling pathway in human diseases remain unclear. This review describes the research milestones of BTLA and HVEM in chronological order and their role in chronic HBV infection.